Evaluasi Kepuasan Pengguna terhadap User Interface Sistem Informasi Akademik Menggunakan Metode End User Computing Satisfaction (EUCS) di Universitas Esa Unggul - Muhammad Rizkie; Qori Halimatul Hidayah (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
This study aims to evaluate the level of user satisfaction with the user interface of the Academic Information System (SIAKAD) at Esa Unggul University using the End User Computing Satisfaction (EUCS) method. This method assesses user satisfaction based on five key dimensions: content, accuracy, format, ease of use, and timeliness. The study employed a quantitative descriptive approach by distributing questionnaires to active Esa Unggul University students as primary system users. The collected data were analyzed using SPSS software to test validity, reliability, and the relationships between variables that influence user satisfaction with the SIAKAD interface. The results show that, in general, users are quite satisfied with the SIAKAD interface, particularly in the ease of use and accuracy dimensions, which obtained the highest scores. This indicates that usability and information accuracy are the dominant factors in creating a positive user experience. However, the timeliness and content dimensions still require further improvement, as they were rated as less optimal in providing fast and comprehensive information. These findings highlight the importance of an intuitive, efficient, and informative interface design in enhancing user satisfaction. This research is expected to serve as a reference for Esa Unggul University in developing and improving its Academic Information System to become more effective, efficient, and user-friendly. Evaluating user satisfaction through the EUCS approach provides valuable insights for system developers to refine the interface, improve information quality, and enhance system responsiveness. Thus, the results of this study are expected to contribute to improving academic service quality and supporting the digitalization of education at Esa Unggul University.